2017
DOI: 10.3390/rs9040320
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Expansion of Boom Crops in Mainland Southeast Asia Using Dense Time Stacks of Landsat Data

Abstract: Abstract:We performed a multi-date composite change detection technique using a dense-time stack of Landsat data to map land-use and land-cover change (LCLUC) in Mainland Southeast Asia (MSEA) with a focus on the expansion of boom crops, primarily tree crops. The supervised classification was performed using Support Vector Machines (SVM), which are supervised non-parametric statistical learning techniques. To select the most suitable SMV classifier and the related parameter settings, we used the training data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 57 publications
0
38
0
1
Order By: Relevance
“…We classified the MODIS time-series following an 'upscaling' approach and extracted training 9 and verification points from seven Landsat-based land-cover change classifications in the region (Hurni et al 2017). Due to the differences in pixel sizes, this operation is usually performed by defining a threshold of a majority cover of the 30m resolution land-cover classes within a MODIS pixel (circa 231m resolution), extracting the MODIS pixels that meet the threshold criteria, and classifying the MODIS data with these samples (Clark et al, 2010;DeFries, Townshend, & Hansen, 1999;Hurni et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We classified the MODIS time-series following an 'upscaling' approach and extracted training 9 and verification points from seven Landsat-based land-cover change classifications in the region (Hurni et al 2017). Due to the differences in pixel sizes, this operation is usually performed by defining a threshold of a majority cover of the 30m resolution land-cover classes within a MODIS pixel (circa 231m resolution), extracting the MODIS pixels that meet the threshold criteria, and classifying the MODIS data with these samples (Clark et al, 2010;DeFries, Townshend, & Hansen, 1999;Hurni et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…We needed to adjust for this imbalance of sample points across the classes. Various scholars have shown that the appropriate amount of sample points for an accurate supervised classification of land-cover change does not only depend on the class area (spatial heterogeneity), but also on the temporal heterogeneity and the classification scheme (spectral-temporal similarity of classes) (Foody & Arora, 1997;Heydari & Mountrakis, 2018;Hurni et al, 2017). To represent temporal heterogeneity, change classes consequently need relatively more sample points despite the small areas they cover.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the expansion of tree crops (particularly rubber) in SAM (Hurni, Schneider, & Heinimann, 2017), many local studies have also reported substantial nontree crop (particularly corn) expansion throughout SAM in the 21st century (e.g. Schmidt-Vogt et al, 2009;Viau, Keophosay, & Castella, 2009;Castella, Jobard, Lestrelin, Nanthavong, & Lienhard, 2012;Heinimann et al, 2013;Kitchaicharoen et al, 2015;Pongkijvorasin & Teerasuwannajak, 2015).…”
mentioning
confidence: 99%
“…Other crops, including cashew, coffee, and pineapple, are grown successfully in mainland Southeast Asia (Hurni et al. ) and could expand into Myanmar. Future agricultural commodity prices, economic liberalization, and suitable climates will determine which crops will expand from 2016 to 2026 and affect large areas of remaining forest.…”
Section: Resultsmentioning
confidence: 99%
“…Although southern Myanmar does not have an optimal climate for oil-palm cultivation (Saxon & Sheppard 2014), it has become a significant driver of deforestation there (Donald et al 2015). Other crops, including cashew, coffee, and pineapple, are grown successfully in mainland Southeast Asia (Hurni et al 2017) and could expand into Myanmar. Future agricultural commodity prices, economic liberalization, and suitable climates will determine which crops will expand from 2016 to 2026 and affect large areas of remaining forest.…”
Section: Land and Agriculturementioning
confidence: 99%